2022
DOI: 10.1038/s41598-022-15785-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nano-sized lead sulfide thin films from Avocado (Glycosmis cochinchinensis) Leaf extracts to empower pollution remediation

Abstract: The translucent and nano-crystalline PbS films were equipped with the CBD techniques on metal substrates by the temperature of 90 °C through aqueous solutions of Lead Nitrate and Thiourea. The XRD phases verify the crystalline property of synthesized thin films that the shape falls in the cubic structures with favourite orientations. It revealed that the prepared material is cubic crystal oriented as (111), (110), (100) and (101) crystal planes. The crystalline size varied between 0.4 and 0.7 nm. The band gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Moreover, this finding is similar to the discoveries of [36][37][38][39] , who described that proliferation in the distance between shallots plants from 5 to 20 cm occasioned a decrease in yields from 36.0 t ha −1 to 23.9 t ha −1 but most (86%) of the bulbs was very low and therefore could not be unmarketable at 5 cm intra-rows-space. Likewise 16 , found that the amount of total yield reduced with the rise in the intra-row-space of shallot.…”
Section: Number Of Leavessupporting
confidence: 89%
“…Moreover, this finding is similar to the discoveries of [36][37][38][39] , who described that proliferation in the distance between shallots plants from 5 to 20 cm occasioned a decrease in yields from 36.0 t ha −1 to 23.9 t ha −1 but most (86%) of the bulbs was very low and therefore could not be unmarketable at 5 cm intra-rows-space. Likewise 16 , found that the amount of total yield reduced with the rise in the intra-row-space of shallot.…”
Section: Number Of Leavessupporting
confidence: 89%
“…Originally the absorption peaks at 664 nm were abundant and superior to the absorption peaks at 615 nm, which provides great alteration between their intensity. After 35 min, these differences are weakened, hence representing that the amount of degradations of monomer is much more sophisticated than that of the dimer [ 60 , 61 ]. Additionally, the decreases in the intensity of the two crests and a small shift in the direction of the blues of the groups positioned at 664 nm were also perceived.…”
Section: Resultsmentioning
confidence: 99%
“…of defect states is very large. Therefore, the emission that occurred in the PL spectra is possibly due to the band tail or from the surface state of the assembled nanoparticles on the substrates [75,76].…”
Section: Pl Analysis Of Se 85 Te 3 Bi 12 Nano-thin Filmsmentioning
confidence: 99%